WDR60-mediated dynein-2 loading into cilia powers retrograde IFT and transition zone crossing - De-Castro, ARG (2022)
The dynein-2 motor complex drives retrograde intraflagellar transport (IFT), playing a pivotal role in the assembly and functions of cilia. However, the mechanisms that regulate dynein-2 motility remain poorly understood. Here, we identify the Caenorhabditis elegans WDR60 homologue, WDR-60, and dissect the roles of this intermediate chain using genome editing and live imaging of endogenous dynein-2/IFT components. We find that loss of WDR-60 impairs dynein-2 recruitment to cilia and its incorporation onto anterograde IFT trains, reducing retrograde motor availability at the ciliary tip. Consistent with this, we show that fewer dynein-2 motors power WDR-60-deficient retrograde IFT trains, which move at reduced velocities and fail to exit cilia, accumulating on the distal side of the transition zone. Remarkably, disrupting the transition zone's NPHP module almost fully restores ciliary exit of underpowered retrograde trains in wdr-60 mutants. This work establishes WDR-60 as a major contributor to IFT, and the NPHP module as a roadblock to dynein-2 passage through the transition zone.